Implementasi Masase Abdominal Effleurage dan Kompres Hangat untuk Penanggulangan Nyeri Dismenore Mahasiswi Kebidanan - Meity Christiani; Hayatur Ridha Sari; Affan Solihin; Hotasi Otana Claudia Lynn (Information Technology and Science (ITScience), 2025)
Astarto writes that dysminore is one of the most common types of menstrual discomfort that affects the lower abdomen, but can also spread to the upper thighs, calves, lower back, and waist. It is necessary to conduct research whether the results of Masase Abdominal Effleurage and Warm Water Compresses can reduce the Intensity of Dysminor Pain. In this study, it will be carried out, but in WHO has never done Masase Abdominal Effleurage and Warm Water Compresses for dysminor pain. Objective: To see if there is an effect on Dysminore Pain before and after the intervention. There was a significant effect of Masase Abdominal Effleurage and Warm Water Compress treatment on reducing the intensity of dysminore pain. Suggestion: Add information and apply it in overcoming pain so that adolescents and health workers can know the correct techniques and procedures in performing Masase Abdominal Effleurage and Warm Water Compresses for dysminor pain.